Application Of The Adams Bashforth-Moulton Method To Coffee Production Quantity Approach - Tarisma, Tantri; Saumi, Fazrina; Nabilla, Ulya (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
Coffee is a type of plantation plant that has long been cultivated so that it has high economic value. Therefore, the authors are interested in approximating the amount of coffee production using the Adams Basforth Moulton method. The Adams Bashforth Moulton method is a way of finding a numerical solution at a certain point of a non-linear differential equation with a known initial value. The differential equation is first solved using the fourth-order Runge Kutta method to obtain four initial solutions which are then substituted into the fourth order Adams Bashforth predictor equation. Furthermore, the approximation value is corrected using the fourth-order Adams Moulton corrector equation. If the relative error is less than the stopping criterion , then the iteration is stopped. The iterations are performed 25 times with an interval of [0,25]. The results of the approximation using the Adams Bashforth Moulton method on the Verhults equation in the approximation show that every year the amount of production increases. The results of the total coffee production in Aceh Province in 2022 will reach 71468 tons and in 2023 it will reach 72966 tons and in 2024 it will reach 74465 tons.